Shock and harmonic response analysis of UAV nose landing gear system with air damper. Issue 1 (1st January 2021) - Son, Lovely; Surya, Muhammad; Bur, Mulyadi; Ubaidillah, Ubaidillah; Dhelika, Radon
Abstract: This research presents a response analysis of a UAV nose landing gear system equipped with an air damper under shock and harmonic excitation. The study begins with dynamic modeling of the UAV landing gear system. The system dynamics consists of a main mass and a wheel mass that are connected to each other by a U-shaped landing gear. The U-shaped landing gear is modeled by a linear spring and dashpot element. The air damper is added to the landing gear to increase the damping. The air damper consists of an air balloon that is connected to the outside via an orifice hole and the connecting pipe. A serial connection of spring, mass, and dashpot elements describes the air damper dynamic model. The simulation study is conducted to evaluate the effect of the landing gear parameters variation on the UAV dynamic response under shock and harmonic excitation. The maximum acceleration and displacement response of the UAV body under shock load is greatly affected by the air balloon cross-sectional area ( Aef ) and the stiffness of the U-shaped landing gear system ( KL ). The harmonic response of the UAV body is evaluated from the ratio between the UAV body displacement amplitude and the base excitation amplitude under harmonic excitation. It is shown that the air balloon cross-sectional area ( Aef ) and the connecting pipe length ( lp ) have a significant effect on the UAV mass displacement ratio. The experimental study is conducted to validate the simulation results. It is shown that the experimental data can verify the simulation results.